IJCM_23A: Long-Term Maternal and Childhood Outcomes Among Women with Post-Partum Depression in Rural and Urban Areas of Khordha, Odisha. - Roy Payel; Subba Sonu Hangma; Singh Arvind Kumar; Behera Binod Kumar; Behera Priyamadhaba; Mohanty Pankaj Kumar; Parmar Arpit (Wolters Kluwer Medknow Publications, 2024)
Background: The prevalence of Postpartum Depression in India varies from 6.8-21.5%. About 5% women reported persistent PPD symptoms even three years after childbirth. PPD increases the suicide risk among mothers. It not only affects the psychological health but also physical health & quality of life of mother. Maternal PPD affects the mother child bonding and also the child growth & development. Objective: To assess the long-term effects of post-partum depression on the mothers and the children at 1 year-5 years. Methodology: We have done a Cohort study with 290 mother-child dyads in both rural and urban area of Khordha, Odisha. Mothers were screened using EPDS for PPD at 6wk to 6 months after delivery. The outcome for mothers and children were assessed at one year to five years after delivery. Chronic depression was assessed with EPDS, confirmed by psychiatric evaluation and suicidality of the mother with SBQ-R; child anthropometric outcomes with WHO growth charts and development with Bayley Scale of Infant and Toddler Neurodevelopment. Results: Among the 62 mothers screened positive for post-partum depression, 18 (29%) were found to have Chronic depression and a significant association was found between post-partum and chronic depression (OR=11.25, CI- 4.60- 27.69, p-value <0.001]. Conclusion: Maternal post-partum depression had significant impact on the maternal and child child-health in the long term.